Intellectual Property Rights : National Policy of India: Patents Trade Marks Copy Rights etc - Sikka, Pawan (New Delhi Synergy Books India, 2017)
India unveiled it's first a comprehensive, National Intellectual Property Rights (NIPRs) Policy-2016, on 13 May 2016, aimed at fostering innovation, cutting delays in clearing patent, trademark and copyright applications; protecting traditional knowledge and encouraging entrepreneurship. It is likely to bring India's IP regime in line with global standards and help improve its ranking in the World Banks Ease of Doing Business Index. The new NIPRs Policy-2016 will speed up the entire registration of patents and trade-marks, etc. The NIPRs Policy-2016 has generated unprecedented responses within and outside India. A critical review of the said NIPRs Policy-2016 has been made by various scholars, published elsewhere and these are compiled and included in this book for the benefit of researchers, policy planners, academicians, legal professionals, etc.
Select Bibliography,Index
Keywords: National Policy -- Intellectual property-government policy -- India